Pelatihan Desain Grafis Media Publikasi Komunitas BPKPKK KAPal berbasis Vektor dan Kecerdasan Buatan - Yulius, Yosef; Bobby Halim; Hestia Rachmat Nunciata Lubis; Yosef Yulius Noor Faiza Febrianti; Muhammad Rivan Hakim (LPPM Universitas HKBP Nommensen, 2025)
This community service activity aims to enhance vector-based graphic design skills and the use of Artificial Intelligence (AI) for publication media among BPKPKK KAPal Community members. In the digital era, the demand for engaging visual content is increasing. However, many communities lack the necessary knowledge of graphic design to support their publications. This training uses a participatory and hands-on approach. Participants learn vector graphic principles using Adobe Illustrator and are introduced to AI technologies like generative AI and AI-assisted tools. The curriculum covers basic illustration, typography, color theory, layout design, and AI-assisted design automation. Results show significant improvement in participants' understanding and skills. They can now create professional posters, brochures, and social media content. Most participants found the training relevant and beneficial. This initiative empowers the community to independently produce quality publication materials and fosters digital literacy and creativity.